Restructuring Russia's industry — Taking stock of the first five years of transition - Harald Sondhof (Intereconomics, 1996)
When the Soviet Union was broken up at the end of 1991, the Russian Federation inherited a large industrial sector which was, however, hardly capable of surviving under market conditions. At about the same time market oriented reforms were begun. What has been accomplished so far? What are the most important tasks that remain to be tackled?
Keywords: 330; System Transformation